2014
DOI: 10.3389/fimmu.2014.00643
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Circulating γδ T Cells in Cancer Patients to Optimize γδ T Cell-Based Immunotherapy

Abstract: The success of γδ T cell-based immunotherapy, where the cytotoxic activity of circulating γδ T lymphocytes is activated by nitrogen-containing bisphosphonates (n-BP), or possibly by bispecific antibodies or the combination of both, requires a profound knowledge of patients’ γδ T cells. A possible influence of radio- or chemotherapy on γδ T cells as well as their reported exhaustion after repetitive treatment with n-BP or their lack of response to various cancers can be easily determined by the monitoring assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…As gdT cells represent a subset of T lymphocytes, 10 we performed an additional anti-CD3 staining with anti-TCR gamma C anti-TCR delta staining on serial sections in 10 patients to confirm the result. As showed in the representative pictures, cells stained by the anti-TCR gd antibody were indeed CD3 C T cells (Fig.…”
Section: Identification Of Gdtilsmentioning
confidence: 88%
See 1 more Smart Citation
“…As gdT cells represent a subset of T lymphocytes, 10 we performed an additional anti-CD3 staining with anti-TCR gamma C anti-TCR delta staining on serial sections in 10 patients to confirm the result. As showed in the representative pictures, cells stained by the anti-TCR gd antibody were indeed CD3 C T cells (Fig.…”
Section: Identification Of Gdtilsmentioning
confidence: 88%
“…Although gdT cells represent a minor subset (1-10%) of T lymphocytes, 10 they generally appear at skin and gut tissues, take a pivotal role in the host immune system, and contribute to either immune-protection or immune-regulation depending on their residual environment. [11][12][13] As in the tumor microenvironment, gdT cells exhibit distinct phenotypes, they can inhibit tumor progression by cytotoxic effect, secretion of perforin/granzyme B, IFN-g and so on, or promote tumor progression by IL-17 secretion and immunosuppressive myeloid cells (MDSCs) recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent efforts have come up with promising directions, such as the Immunogram [135], a collection of parameters describing the immune status, mutational burden, etc., of a tumor as an approach to identify tumors that would be responsive to immune-oncology therapies. Such an approach could be adapted to include T cell-subsets, such as Vγ9Vδ2 T cells, in the prediction of patient immune cell status and personalized therapy [136]. Indeed, Cibersort computational analyses have already shown that, with the right resolution, we might be able to discriminate and quantify immune cell subsets down to Vγ9Vδ2 T cells from sequencing data [39,40].…”
Section: Towards Precision Immune-oncologymentioning
confidence: 99%
“…We (Kabelitz group) have established a system to accurately determine absolute numbers of circulating Vδ1 and Vδ2 γδ T cells from a small sample of whole blood. This method enabled us to determine a threshold number of Vδ2 T cells per microliter blood below which no cytotoxic activity toward pancreatic adenocarcinoma tumor targets could be triggered by pAg or Her2-Vγ9 tribody ( 48 ). Another important step for the application of γδ T cell-based immunotherapy involves identifying the antigenic ligands recognized by γδ T cells on tumor cells as they may potentially be used as agonistic drugs either ex vivo for γδ T cell expansion or in vivo for active vaccination trials.…”
Section: γδ T Cells In Tumor Immunitymentioning
confidence: 99%